2020
DOI: 10.3390/rs12213624
|View full text |Cite
|
Sign up to set email alerts
|

Combining SfM Photogrammetry and Terrestrial Laser Scanning to Assess Event-Scale Sediment Budgets along a Gravel-Bed Ephemeral Stream

Abstract: Stream power represents the rate of energy expenditure along a stream reach and can be calculated using topographic data acquired via structure-from-motion (SfM) photogrammetry and terrestrial laser scanning (TLS). This study sought to quantitatively relate morphological adjustments in the Azohía Rambla, a gravel-bed ephemeral stream in southeastern Spain, to stream power (ω), critical power (ωc), and energy gradients (∂ω/∂s), along different reference channel reaches of 200 to 300 m in length. High-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 52 publications
(59 reference statements)
2
20
0
1
Order By: Relevance
“…Besides radioactive contamination of the landslide itself, the run-out or generated impulse wave may further cause damage to nearby houses, infrastructure, or pasture land [24,57]. It was demonstrated that the landslide could cause considerable change in water quality with large increases in the concentration of suspended solids and toxic elements [33,39,58]. Therefore, the instantaneous release of Pb-210 that is associated with the release of the suspended sediment was studied in this paper.…”
Section: Mass Transport Of Radionuclidesmentioning
confidence: 99%
“…Besides radioactive contamination of the landslide itself, the run-out or generated impulse wave may further cause damage to nearby houses, infrastructure, or pasture land [24,57]. It was demonstrated that the landslide could cause considerable change in water quality with large increases in the concentration of suspended solids and toxic elements [33,39,58]. Therefore, the instantaneous release of Pb-210 that is associated with the release of the suspended sediment was studied in this paper.…”
Section: Mass Transport Of Radionuclidesmentioning
confidence: 99%
“…Often, these bed-forms are composed on poorly sorted sediments with mixed grain sizes (sand, gravel, and pebbles). Deposits of different textures alternate in depth with a general tendency to increase in grain size from the bottom up [11]. This alluvial fill rests mainly on a Miocene marl substrate, the fine texture of which contrasts with that of the overlying coarse detrital materials.…”
Section: Study Area: Geomorphological and Climatic Settingmentioning
confidence: 99%
“…Electrical resistivity tomography (ERT) is a non-invasive method of rapid application, which is usually used to generate models of distributions of electrical properties of the subsurface, from which the geological structure and hydrogeological variations can be inferred [7][8][9]. Additionally, ERT can be employed to map spatial variations of qualities within a mineral deposit in 3D [10,11]. Several authors conducted ERT surveys to study loose materials, assess mine tailings, and so forth [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although a photograph usually provides the interpretation of any visible element (there are many cases where other types of images result in being more convenient [12]), the laser contributes its geometry with a very high degree of precision, automatically and in a short space of time [13][14][15][16][17]. Due to the laser scanner, the application of both techniques together allows for non-invasive reverse engineering processes where no contact with the element is necessary [18][19][20][21][22], which is especially relevant in heritage studies [23]. Cultural heritage is one of the fields with more different applications of combined techniques (as many different sciences are applied together in restoration works).…”
Section: Introductionmentioning
confidence: 99%